PENGARUH BERBAGI INFORMASI DAN HUBUNGAN JANGKA PANJANG TERHADAP KINERJA RANTAI PASOKAN DAN KEUNGGULAN BERSAING (Studi Pada IKM Olahan Rendang Kota Payakumbuh) - Shela, Hasm Riaufa; Rio g, Marpaung J.M.; Samsir, Samsir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine whether there is a significant influence between information sharing and long-term relationships on supply chain performance and the effect of supply chain performance on competitive advantage in the small and mediumsized at rendang industry in Payakumbuh. Respondents in this study are 43 members of IKM Rendang Payakumbuh that registered at the Department of Industry and Manpower. The data collected was first tested with validity and reliability tests, then the validated data were processed using SEM-PLS with Wrap-PLS 7.0 software. The results of data processing showed that there is an insignificant influence between information sharing on supply chain performance and there is a significant positive relationship between long-term relationships and supply chain performance. There is also a significant positive relationship between supply chain performance and competitive advantage.Keywords: Information sharing, long-term relationships, supply chain performance, competitive advantage, and Wrap-PLS.